2011
DOI: 10.1186/1471-2377-11-1
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid and antiviral therapy for Bell's palsy: A network meta-analysis

Abstract: BackgroundPrevious meta-analyses of treatments for Bell's palsy are still inconclusive due to different comparators, insufficient data, and lack of power. We therefore conducted a network meta-analysis combining direct and indirect comparisons for assessing efficacy of steroids and antiviral treatment (AVT) at 3 and 6 months.MethodsWe searched Medline and EMBASE until September 2010 using PubMed and Elsviere search engines. A network meta-analysis was performed to assess disease recovery using a mixed effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
13

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 34 publications
1
88
0
13
Order By: Relevance
“…73 It is estimated that 26 patients would require treatment with the combination therapy to achieve 1 better facial nerve outcome than with steroid therapy alone. 78 In summary, antiviral therapy in addition to steroid therapy has not been proven to be of benefit in the treatment of Bell's palsy in large, high-quality clinical trials, although a small benefit cannot be completely excluded. Due to the potential of a small benefit in facial nerve functional recovery and the relatively low risk of antiviral therapy, the GDG concluded that patients may be offered combination therapy if treated within 72 hours of onset of Bell's palsy, with a large role for shared decision making.…”
Section: -78mentioning
confidence: 99%
“…73 It is estimated that 26 patients would require treatment with the combination therapy to achieve 1 better facial nerve outcome than with steroid therapy alone. 78 In summary, antiviral therapy in addition to steroid therapy has not been proven to be of benefit in the treatment of Bell's palsy in large, high-quality clinical trials, although a small benefit cannot be completely excluded. Due to the potential of a small benefit in facial nerve functional recovery and the relatively low risk of antiviral therapy, the GDG concluded that patients may be offered combination therapy if treated within 72 hours of onset of Bell's palsy, with a large role for shared decision making.…”
Section: -78mentioning
confidence: 99%
“…Since most of these forms in childhood recover spontaneously, aim of the drug therapy is to minimize the possibility of incomplete resolutions and reduce the risk of sequelae, such synkinesis, autonomic dysfunctions (e.g., crocodile tears), facial spasms [26] . When Bell's palsy occurs in adults, it is well known that glucocorticoids in combination with antiviral therapy (acyclovir or valacyclovir) are recommended [27][28][29][30] . In children, the use of oral corticosteroids is recommended preferably within 3 d from onset of symptoms (the suggested treatment regimen is prednisone 1-2 mg/kg per day for 10 d, gradually decreasing the dose) [13,31] as the majority of patients improves in the first three weeks [32] , although several studies did not find significant differences between the outcomes of children treated with corticosteroids and not [20,[33][34][35] .…”
Section: Drug Therapymentioning
confidence: 99%
“…A recent network meta-analysis aimed to overcome the difficulties in pooling results from studies with different treatment regimens by combining direct and indirect comparisons 11. The systematic review identified six studies (published up to September 2010) involving 1,805 subjects.…”
Section: Drug Treatmentmentioning
confidence: 99%